KITOSAN SEBAGAI ABSORBEN IMPURITY DALAM PEMBUATAN AGAR MEDIA - PIPIH SUPTIJAH; LINAWATI HARDJITO; JOHN HALUAN; MAGGY T WIJAYA (Akuatik: Jurnal Sumberdaya Perairan, 2010)
Existing problem in production process for fulfilling International standard still taking as a problem for Indonesian product, therefore need modification of production process which can match with the commercial standard even also International standard. One of alternative of the production process that is through input of chitosan as impurity absorbent in its extraction, so can get high quality product of jelly for medium, and others. This research aim to application of chitosan as absorbent, to produce jelly with simple method and without chemicals, and characterize of jelly and also compare it to commercial bakto ( difco). Method used in this research is using impurity absorbent by chitosan in extraction process through chitosan filtration which obtainable absorbs can directly acquire jelly extract in order to clear of pollutant omit continued with draining. Result of jelly extract analysis showed characteristic quality of jelly produced which is viscosities 9,1cPs - 12,5cPs ( bakto 17,5cPs), value of TPC 1,8x101 CFU ( bakto 1,1x102 CFU), gel strength 261,26 gF - 297,8 gF with irrigate rate 20,9% - 23% higher than bakto jelly 16,9%. Bacterium growth through TPC test at chitosan treatment 0,1% obtained TPC value is 1,8x101 colony, while TPC value in bakto jelly is 1,1x102 colony. Sulphate value is very determine and difficult enough to decrease it. Sulphate value of jelly of chitosan absorbs treatment showed vary value, from 0,15% until 0,28%, but statistically do not differ reality. Sulphate value is lower than jelly without treatment ( 0,65%) and also is lower than bakto jelly as standard (0,35%)